Alternative Mechanisms of Service Delivery : Blue Print for Promoting AMSD - World Bank (Washington, DC, 2013)
This Report presents a plan for improving service delivery in regional governments using a set of strategies that are commonly found in an approach described as 'Alternative Mechanisms of Service Delivery' (AMSD). The report has been prepared as part of a contract between the Decentralization Support Facility (DSF) and Hickling Corporation of Canada. This report aims to outline the most important programs/activities that central government might undertake to help regional governments systematically improve service delivery, which after all, is one of the key objectives of the decentralization policy. It hopefully provides the basis for a system of improving service delivery. The objectives in relation to promoting AMSD within regional governments are: assistance to government in the rationalization of different institutional arrangements for the delivery of sub-national public services; and aid in the development and implementation of new (contracting) methods for service delivery. This final section is in recognition that planning is nothing without good implementation and learning from experience.